Burden of Middle East respiratory syndrome coronavirus infection in Saudi Arabia - Al-Raddadi, Rajaa M.; Shabouni, Omaima I.; Alraddadi, Zeyad M.; Alzalabani, Abdulmohsen H.; Al-Asmari, Ahmad M.; Ibrahim, Adel; Almarashi, Abdullatif; Madani, Tariq A. (Journal of infection and public health, 2020)
MERS-coronavirus infection is currently responsible for considerable morbidity and mortality in Saudi Arabia. Understanding its burden, as an emerging infectious disease, is vital for devising appropriate control strategies. In this study, the burden of MERS-CoV was estimated over 31months period from June 6, 2012 to January 5, 2015. The total number of patients was 835; 528 (63.2%) patients were male, 771 (92.3%) patients were ≥25 years of age, and 210 (25.1%) patients were healthcare workers. A total of 751 (89.9%) patients required hospitalization. The median duration between onset of illness and hospitalization was 2 days (interquartile range, 0–5). The median length of hospital stay was 14 days (IQR, 6–27). The overall case fatality rate was 43.1%. Basic reproductive number was 0.9. Being Saudi, non-healthcare workers, and age ≥65 years were significantly associated with higher mortality. In conclusion, MERS-CoV infection caused a substantial health burden in Saudi Arabia.